Schiff Bases of Triethylenetetramine as Corrosion Inhibitors of Zinc in Hydrochloric Acid - Shah,M.D. (2011)
The performance of triethylenetetramine-tribenzylidene (TTTB) and triethylenetetramine-trisalicylidene (TTTS) as corrosion inhibitors for zinc in hydrochloric acid is investigated. At lower concentrations, both inhibitors accelerate the attack but inhibit corrosion at higher concentrations, e.g., 96-100% with 1.0% concentration in 0.5 M and 1.0 M HCl. The efficiency of TTTB decreases while that of TTTS remains almost constant (≥ 99.7%) up to 120 minutes and in the temperature range 35 - 65 ºC. The activation energies are higher in inhibited than in plain acid with both inhibitors. The free energy of adsorption (ΔGads) and heat of adsorption (Qads) are negative, which suggests that there is spontaneous adsorption on metal surface, and from the values of (ΔGads) and (Qads), the values of entropy of adsorption (ΔSads) were calculated. Galvanostatic polarization shows that corrosion is under mixed control with predominance of the cathodic part. In uninhibited 1.0 M HCl, complete cathodic protection is achieved at a current density of 4.2224 Adm-2, but in presence of these inhibitors, much lower current densities are required. Plot of log (θ/1-θ) versus log Cinh gives a straight line, suggesting that inhibitors cover both the anodic and cathodic regions through general adsorption following Langmuir isotherm. The mechanism of inhibition has been proposed.